2014
DOI: 10.4301/s1807-17752014000200005
|View full text |Cite
|
Sign up to set email alerts
|

Information Technology Governance in Public Organizations: How Perceived Effectiveness Relates to Three Classical Mechanisms

Abstract: Information technology (IT) governance has received a lot of attention lately, with a growing strategic importance currently being given to IT by both public and private organizations. This justifies the existence of a body of scientific literature on IT governance, to which this paper belongs and makes an attempt to contribute to. Towards that end, an empirical study was performed involving 57 public organizations of the Brazilian federal administration, examining the relationship between three governance mec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 20 publications
1
2
0
1
Order By: Relevance
“…Mechanisms structure appear to be more effective among universities such IT Steering Committee, IT Strategy Committee. This hypothesis's results are consistent with a study conducted by [42], [8], [29], [26], [46], [30] who found that Mechanism structure in IT Steering Committee, IT Strategy Committee have positive effect ITG. The Head of the Information System Center/IT Organizational Structure defining roles and responsibilities for making IT decisions and for enabling contacts between business and IT management decision-making functions.…”
Section: B Hypotheses Testingsupporting
confidence: 92%
See 1 more Smart Citation
“…Mechanisms structure appear to be more effective among universities such IT Steering Committee, IT Strategy Committee. This hypothesis's results are consistent with a study conducted by [42], [8], [29], [26], [46], [30] who found that Mechanism structure in IT Steering Committee, IT Strategy Committee have positive effect ITG. The Head of the Information System Center/IT Organizational Structure defining roles and responsibilities for making IT decisions and for enabling contacts between business and IT management decision-making functions.…”
Section: B Hypotheses Testingsupporting
confidence: 92%
“…The study of the effectiveness of IT governance mechanisms has resulted in the results of studies on how IT governance mechanisms affect the effectiveness of information technology governance [4], [26], [29]. Research by [30] examines the relationship between three governance mechanisms -the IT steering committee, the IT solution manager, and the IT investment portfolio management process and the effectiveness of IT governance. Using the method of sending questionnaires to 180 federal government employees, the results of the study show that there is a positive correlation between the IT steering committee and the IT solution manager and the effectiveness of IT governance.…”
Section: Effectiveness Itgmentioning
confidence: 99%
“…This is to ensure better decision making as IT steering committee is the expert in IT domain. Heindrickson and Carlos (2014) suggest that to have better IT governance, organisation must have an effective IT steering committee which consists of managers and executives from business and IT fields. The IT steering committee is responsible for setting strategic and numerical goals, making investments, approving policies, and setting priorities.…”
Section: It Steering Committeementioning
confidence: 99%
“…Project prioritization and selection requires the defining a decision-making structure and establishing its governance (Heindrickson and Santos, 2014). Liesiö and Salo (2012) show that projects are usually selected based on uncertain future consequences, as information based on scenario probabilities or decision-maker risk preferences are hard to obtain.…”
Section: Bibliographic Reviewmentioning
confidence: 99%